In tokhang, we trust - De Vera, China Pearl Patria M. (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/lagda/article/view/8157/7120
Keywords: Oplan Tokhang; Tagalog short stories; Extrajudicial executions